The Effect of the 5E Learning Cycle Model on the Critical Thinking Skills of Junior High School Students in Learning Science - Amaliyah, Tsabitah; Rusdianto, Rusdianto; Supeno, Supeno (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
Critical thinking skills are very important to be acquired by the students in the 21st century. In science learning, students are required to think critically. However, studentsâ€™ critical thinking skills at the junior high school level are included in the low category. The 5E learning cycle model is the learning model that is considered can train the student’s critical thinking skills optimally. The purpose of this study was to examine the effect of the 5E learning cycle model on junior high school students’ critical thinking skills in science learning and to describe the improvement of junior high school studentsâ€™ critical thinking skills. This type of research is experimental research with a quasi-experimental design and nonequivalent (pretest and posttest) control-group design. The results of the study for the effect test using the independent sample t-test obtained the value of Sig. (2-tailed) of 0.016 which means <0.05. The implication is that the 5E learning cycle model has a significant effect on the thinking skills of junior high school students in learning science. For the improvement test using N-Gain, an average N-Gain of 0.5875 was obtained which was included in the moderate category, then the results of the paired sample t-test obtained a Sig value. (2-tailed) of 0.000 which means <0.05. The conclusion was the 5E learning cycle model has a significant effect on junior high school studentsâ€™ critical thinking skillsÂ in science learning and it can improve junior high school students’ critical thinking skills in the moderate category.